2014
DOI: 10.1103/physreva.90.063617
|View full text |Cite
|
Sign up to set email alerts
|

Critical exponents for an impurity in a bosonic Josephson junction: Position measurement as a phase transition

Abstract: We use fidelity susceptibility to calculate quantum critical scaling exponents for a system consisting of N identical bosons interacting with a single impurity atom in a double well potential (bosonic Josephson junction). Above a critical value of the boson-impurity interaction energy there is a spontaneous breaking of Z2 symmetry corresponding to a second order quantum phase transition from a balanced to an imbalanced number of particles in either the left or right hand well. We show that the exponents match … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Recent realizations of this transition include both an actual superradiant transition in an optical cavity filled with an atomic BEC pumped from the side by a laser [77], and simulations in trapped ion systems [78]. In our case, the two levels of the impurity simulate the first two levels of the harmonic oscillator and, remarkably, this is enough to capture the critical properties of the Dicke model which are determined by the regime where the electromagnetic field is barely excited [69]. Another similarity between the Dicke model and the boson-impurity model is that both display regular dynamics in the normal phase and chaotic dynamics in the symmetry broken phase [68,79].…”
Section: Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent realizations of this transition include both an actual superradiant transition in an optical cavity filled with an atomic BEC pumped from the side by a laser [77], and simulations in trapped ion systems [78]. In our case, the two levels of the impurity simulate the first two levels of the harmonic oscillator and, remarkably, this is enough to capture the critical properties of the Dicke model which are determined by the regime where the electromagnetic field is barely excited [69]. Another similarity between the Dicke model and the boson-impurity model is that both display regular dynamics in the normal phase and chaotic dynamics in the symmetry broken phase [68,79].…”
Section: Modelmentioning
confidence: 96%
“…Finite values of U excite particles into the antisymmetric mode and as |U | → ∞ the two modes become equally occupied so that Ŝx = 0. In the thermodynamic limit N → ∞ the QPT becomes sharp such that Ŝx = 0 for Λ > Λ c (normal phase) and takes finite values for Λ < Λ c (Z 2 symmetry broken phase) [68,69,80]. Therefore Ŝx is a good order parameter for this transition.…”
Section: Modelmentioning
confidence: 99%
“…Here, the polaronic behavior should strongly depend on the involved interactions and an intriguing prospect would be to engineer specific entangled polaron states in certain interaction regimes with an additional knob provided by the interspecies mass-imbalance. Moreover, we should also emphasize that these hybridized systems are of further interest due to the fact that one subsystem (impurity) lies in the deep quantum regime while the other one (medium) can be potentially described semi-classically [72][73][74][75][76][77]. For instance, it has been demonstrated that following an impurity-bath interaction quench leads to chaotic signatures in the dynamics of the bath accompanied by significant coherence losses [77].…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we investigate a binary ultracold atomic mixture made of a single impurity and a noninteracting many-body bosonic ensemble that are confined within a 1D DW potential. Unlike most of the previous studies where the focuses are put on the weak-interacting regime, rendering the impurity being restricted into the lowest two modes of the DW potential [51][52][53][54][55][56], our discussions are not restricted to such a scenario. Specifically, we study the onset of the chaos for the majority bosonic species due to the presence of the impurity and put particular emphasis on the its dynamical response upon a sudden quench of the impurity-Bose interaction strength.…”
Section: Introductionmentioning
confidence: 99%